Programma: 13 augustus Ragga Dance Hall; 20 augustus My Dying Bride, Anathema, At The Gate; 21 augustus Club locale; 26 augustus Arrested Development
Programma: 13 augustus Ragga Dance Hall; 20 augustus My Dying Bride, Anathema, At The Gate; 21 augustus Club locale; 26 augustus Arrested Development.